Digital economy, green finance, and economic resilience - Jianqi Zhang (PLoS ONE, 2025)
With the rapid development of digital technology, the digital economy has become an important force to promote economic growth and drive innovation, and to enhance economic quality and ecological efficiency through green finance. Additionally, green finance, as an important means to achieve resource and environmental sustainability, has received increasing attention and importance from the international community. This study explores how the digital economy and green finance contribute to economic resilience using panel data from 30 provinces and cities in China from to 2011–2023. The development of the digital economy can effectively promote economic resilience, and green finance plays a significant mediating role between the digital economy and economic resilience. In this regard, China’s economic resilience must be enhanced by strengthening the construction of digital infrastructure, promoting innovation and the development of green finance, and formulating a policy environment conducive to the development of green finance.